Achieving MDGs 4 and 5 : Egypt's Progress on Maternal and Child Health - Sarker, Intissar (World Bank, Washington, DC, 2015)
Egypt is a lower-middle-income country with a GNI per capita (PPP) of US$ 5,654 in 2012. Since the Arab Spring, Egypt s economic growth has slowed to 0.6 percent in 2012. Half of Egypt s 82.54 million people live in rural areas. Poverty is concentrated in Upper Egypt (the southern region). As of 2009, 43.7 percent of Upper Egypt s rural population was living in poverty. Egypt has made considerable progress in improving maternal and child health. According to interagency estimates, child mortality declined from 86 to 21 deaths per 1,000 live births between 1990 and 2012 a 75.4 percent drop, that exceeds Egypt s target for MDG 4. Egypt also successfully reduced neonatal mortality by 65 percent during the same period. Egypt s maternal mortality ratio (MMR) declined from 120 to 45 deaths per 100,000 live births between 1990 and 2013 a 62 percent decrease, also exceeding its MDG 5 target. However, recent political events in the country bring into question the long-term sustainability of gains if conditions do not improve. This note explores the actions Egypt has taken to reduce child and maternal mortality, with a focus on policies and programs.